The Effect of Pricing and Product Quality on Purchase Decisions on PT. Gunung Sentosa Sumatera Utama Industri - Kristin Sanjayati; Robin Robin (Jurnal Mantik, 2022)
This study aims to determine the effect of price and product quality on purchase decision of PT. Gunung Sentosa Sumatera Utama Industri. This type of research is explanatory research. The population in this study were all customers of PT. Gunung Sentosa Sumatera Utama Industri, with a total of 213 customers. The technique for determining the sample is using the slovin technique with a tolerance level of 5% so that a total of 139 samples are obtained. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that price and product quality partially or simultaneously have a positive and significant effect on purchase decision of PT. Gunung Sentosa Sumatera Utama Industri. Based on the results of this study, the implications for management are to further improve price and product quality.